Interpretable machine learning prediction of coalbed methane content and depth-dependent predictive contributions in shallow and medium-deep reservoirs: A case study of the Qinshui Basin - Kun Bai; Jian Shen; Wei Li; Sijie Feng; Chen Li; Jiuqing Li; Shuting Cheng; Chenlong Wang (Fuel, 2027)

First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Heat-tolerant flexible pressure sensor with ultra-broad linear range for high-temperature object recognition - Yugang Chen; Shasha Wang; Shuting Xie; Haopeng Wang; Qifei Lv; Xun Fu; Huan Gao; Jiangtian Tan; Yuyu Liu; Linghai Xie (Chemical Engineering Journal, 2026)

Effects of localized heating body segments on the effectiveness of personal comfort systems in cold environments: A meta-analysis - Longde Chen; Kun Zhou; Shuting Li; Yankai Zhao; Hao Chen; Yi Xu (Energy and Buildings, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Enabling fast Li+ transport in cellulose nanocrystals polymer electrolytes via grafting flexible acrylates for stable solid-state lithium metal batteries - Xinyan Lv; Shuting Liu; Lin Peng; Sheng Liu; Zhenkun Liu; Zuyun Chen; Xiaoyuan Yu (Carbohydrate Polymers, 2026)

Causal machine learning uncovers thresholds and seasonal reversal in landscape-meteorology-driven urban Heat-PM₂.₅ coupling - Yiqi Yu; Jie Xu; Shuting Chen; Sidong Huang; Licheng Feng; Wei Cao; Wen Zhou (Sustainable Cities and Society, 2026)

A global analysis of the bidirectional relationship between biodiversity conservation and poverty reduction - Shuting Chen; Felix Eigenbrod; Craig Hutton; Robert Holland (Global Environmental Change, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Integrated biological sulfidogenic process: Synergizing sulfate and elemental sulfur reduction for metal-laden wastewater treatment - Jiahua Guo; Junjie Han; Chenxin Zhang; Hao Li; Cheng Li; Shuting Chen; Yibo Wang; Yu Li; Feng Jiang (Water Research, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Distinct riverine plastispheres and microplastic-specific community complexity in the near-bottom benthic habitat under natural hydrological conditions - Yuanyu Cao; Songze Chen; Shuting Zhao; Bingwen Liu; Tao Yuan; Jiane Zuo; Mui-Choo Jong (Journal of Hazardous Materials, 2026)

Doped NiFe2O4 spinel oxygen carriers for enhanced H2 production in photo-assisted chemical looping reforming with water splitting under mild conditions - Yunkun Zhao; Shuting Min; Yibo Guo; Guangxuan Chen; Rongjing Wang; Xiaolong Xu; Jing Huang; Yang Hu; Tingting Xu; Xun Wang (Journal of Cleaner Production, 2026)

Limitations of satellite precipitation products in capturing extreme precipitation events: An object-based evaluation over China - Hongji Gu; Dingtao Shen; Jinming Chen; Chunxiao Zhang; Shuting Xiao; Fei Yu (Atmospheric Research, 2026)

Study on the Effects and Mechanisms of Resveratrol in Improving Cognitive Impairment in Aβ1−42-Induced Alzheimer’s Disease Model Mice - Chu Zhang; Yunhan Ma; Zhidan Shi; Xinqi He; Jiayi Hu; Shuting Chen; Hao Wu; Meng Tian; Chuang Yan; Mengtao Xing; Ling He (Journal of Neuroimmune Pharmacology, 2026)

Influence of beach nourishment on the ecological rehabilitation of sandy beaches: A case study of Beihai Silver Beach on the southern coast of China - Hongshuai Qi; Min Chen; Shuting Zeng; Shunling Wu; Xiaoli Song; Haiqin Duan; Jiayu Li; Feng Cai (Ocean & Coastal Management, 2026)

Mixed exposure to brominated flame retardants adversely affects vaccine-induced antibody titers: Risk prioritization and benchmark dose modeling - Zihui Zhao; Chi Zhang; Xueyu Chen; Yongheng Yan; He Jiao; Xianhao Wang; Ruxu Yan; Yiqian Wang; Meng Liu; Xianfeng Yue; Yuqian Sui; Xia Li; et al. (Toxicology Letters, 2026)

Serine metabolism hijacks radiotherapy-driven antitumor immunity via suppressing STING-dependent DNA sensing - Xiaochuan Hong; Yuanqin Yang; Lingling Wu; Shuting Xu; Chao Yang; Tong Cui; Qishan Wang; Zhihao Wu; Xueni Yu; Qi Chen; Hanyu Hong; Qianjiang Chen; et al. (Science Bulletin, 2026)

Calcium signaling and hormonal regulation mediate Trichoderma harzianum NDT-1-induced resistance against postharvest gray mold in tomato - Yawen Wang; Zhenshuo Wang; Ruoyu Wu; Shuting Chen; Baojuan Sun; Weijie Xu; Tao Li; Yuyang Zhang; Yanwei Hao; Chao Gong (Postharvest Biology and Technology, 2026)

Correction: Eradication Efficacy of Antimicrobial Peptide CRAMP-34 Against Mixed-Species Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - Huiming Hu; Miao You; Tengyue He; Lihong Yuan; Fan Wang; Yanshuang Huang; Huizhen Zhu; Ruiqi Chen; Shuting Liu; Wei Wei; Hongzao Yang; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2026)

Study on the improvement effect and mechanism of resveratrol on cognitive impairment in tau mutant adenovirus-induced alzheimer’s disease model mice - Shuting Chen; Kexuan Zhao; Zhidan Shi; Chu Zhang; Hao Wu; Meng Tian; Yi Sun; Ling He (Psychopharmacology, 2026)

Experimental study on methane reforming coupled with thermochemical water splitting using kilogram scale oxygen carriers for co-production of hydrogen and syngas - Rongjing Wang; Xiaolong Xu; Guangxuan Chen; Yunkun Zhao; Yibo Guo; Shuting Min; Tingting Xu; Xun Wang (Fuel, 2026)

Fabrication of monovalent cation perm-selective membranes via quaternized poly(aryl ether sulfone) modification for efficient Li+/Mg2+ separation - Shuting Zhang; Yunxiang Ouyang; Khalznkhuu Otgonlkhagva; Jiaze Li; Jialin Lv; Na Li; Zhaoxia Hu; Shouwen Chen (Desalination, 2026)

Boosting sensitivity in self-powered visible-blind UV detectors through gradient oxide-semiconductor/perovskite heterostructure - Xuehu Luo; Zhanwei Liu; Junnan Mai; Huasheng Chen; Junpeng Deng; Shuting Cai; Wei Zhong; Sunbing Deng; Guijun Li; Hoi-sing Kwok; Jianfeng Zhang; Yuan Liu (Chemical Engineering Journal, 2026)

Eradication Efficacy of Antimicrobial Peptide CRAMP-34 Against Mixed-Species Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - Huiming Hu; Miao You; Tengyue He; Lihong Yuan; Fan Wang; Yanshuang Huang; Huizhen Zhu; Ruiqi Chen; Shuting Liu; Wei Wei; Hongzao Yang; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2026)

Dose–dependent effects of ferrous sulfate on carbon–nitrogen stabilization and microbial functional pathways in manure composting - Haili Si; Shuting Tang; Lei Li; Shengbo Wang; Junzhi Chen; Yulong Li; Lidong Ji (Journal of Environmental Management, 2026)

Insights into the mechanism of nutty aroma formation by Staphylococcus saprophyticus in fermented sausages - Jikun He; Youqin Duan; Shuting Yang; Fidel Toldrá; Jiong Zheng; Muying Du; Linlin Wang; Nodali Ndraha; Shuyao Wang; Juan Chen (International Journal of Food Microbiology, 2026)

Anammox dominated As(V/III) speciation during long-term anaerobic conditions - Taicong Liu; Shuting Tang; Yingpeng Sun; Zhongtao Lao; Daijie Chen; Ming Ao; Haojie Qu; Chao Jin; Liying Lan; Roland Bol; Miaoyue Zhang; Yingjie Cao; et al. (Soil Biology and Biochemistry, 2026)

Optimisation study of a geometric-VOF model based on elementary symmetric polynomial and adaptive time-step Crank-Nicolson method - Ziming Xu; Yanjun Liu; Zaibin Lin; Shuting Huang; Hao Chen; Gang Xue (Ocean Engineering, 2026)

Long-term assessment of natural mineral-based electrochemical systems for concurrent wastewater treatment and nutrient recovery - Yukun Xing; Shuting Chen; Baile Wu; Xiyuan Feng; Ke Hu; Xiaoxiang Zhang; Junyu Zhou; Jingsheng Shi; Yafei He; Peng Li; Zhengyu Jin (Journal of Water Process Engineering, 2026)

Airborne particles increase skin damage through photoinduced release of superoxide anion and hydroxyl radicals - Xiaotong Xu; Shuting Wei; Qing’e Shan; Chuncheng Chen; Sijin Liu; Juan Ma (Journal of Environmental Sciences, 2026)

The impact of renewable power flow and its structure changes on metal consumption in China - Chen Weiming; Lu Wenjie; Chi Shuting (Resources, Conservation and Recycling, 2026)

Plastic-derived dissolved organic matter amplifies the bioavailability and toxicity of short-chain chlorinated paraffins in Chlorella vulgaris - Changqing Yao; Shuting Fang; Yiquan Huang; Baohua Huang; Chao Chen; Qijun Ruan; Weixin Liang; Shenghong Yang; Shuqin Liu (Journal of Hazardous Materials, 2026)

Mechanistic insights into organic acid-enhanced polycyclic aromatic hydrocarbon release from soil: Disruption of metal cation bridges and charge-assisted hydrogen bonds - Shuting Wei; Yue Yuan; Weifeng Chen; Jinzhi Ni; Huiying Zhang; Meiyu Yang; Ran Wei (Environmental Research, 2026)

Simultaneous identification and detection of five antibiotics using a machine learning-enhanced glass capillary SERS sensor - Sisi Tang; Ruili Li; Yujun Cheng; Shuting Huang; Qi Liu; Xiaoqing Chen (Journal of Hazardous Materials, 2026)

Correlation analysis of monosaccharide composition and in vitro antioxidant and hypoglycemic activities of Tremella fuciformis spore polysaccharides - Jianqiu Chen; Xiaoyu He; Shuting Zhou; Yujie Chen; Chunyuan Kong; Yating Deng; Shikai Ruan; Chengzhen Gu; Shujing Sun (Food Chemistry, 2026)

Evaluation of three scale-aware planetary boundary layer schemes in WRF Model during Beijing 2022 Winter Olympics - Yuhuan Li; Min Chen; Shiguang Miao; Gaojie Zhang; Qianqian Huang; Shuting Zhang (Atmospheric Research, 2026)

Chemical composition, source apportionment and formation mechanisms of PM2.5 in urban and background areas of northwestern China - Kai Cheng; Yuting Zhong; Xinchun Liu; Xia Li; Maulen Ayitken; Shuting Li; Hongna Chen; Bingbing Leng; Wang Zhang; Haiyang Cai (Atmospheric Pollution Research, 2026)

Ultra-stable crease-structured paper pressure sensor with ultra-low detection limit for wind sensing and real-time texture recognition - Yugang Chen; Shasha Wang; Yan Li; Mengyu Cao; Xun Fu; Shuting Xie; Jiangtian Tan; Huan Gao; Linghai Xie (Chemical Engineering Journal, 2025)

Paper-based perovskite artificial neuromorphic retina: Flexible sensing-processing architecture with dual-mode encryption - Zhanwei Liu; Jianfeng Zhang; Junnan Mai; Xuehu Luo; Yanting Chen; Yuhao Ruan; Dengyun Lei; Shuting Cai; Yao Ni; Guijun Li; Jing Wang; Qifan Xue; et al. (Chemical Engineering Journal, 2025)

Microplastic exposure induces structural hyperplasia in the gill tissue of grass carp (Ctenopharyngodon idellus) through immunosuppression, metabolic disruption, and structural damage - Fubin Zhang; Xueting Chen; Shuting Huang; Zhendong Qin (Aquatic Toxicology, 2025)

FAK mediates mechanical signaling to maintain epithelial homeostasis through YAP/TAZ-TEADs - Yang Peng; Qiuyun Yuan; Shuting Zhou; Jianguo Gan; Zhengzhong Shen; Xiaoqiang Xia; Yuchen Jiang; Qianming Chen; Yao Yuan; Gu He; Qiang Wei; Xiaodong Feng (Histochemistry and Cell Biology, 2025)

Radial oxygen loss of Typha latifolia outperforms microbial effects in heavy metal(loid) stabilization - Taicong Liu; Liying Lan; Yuanyuan Li; Daijie Chen; Ming Ao; Shuting Tang; Haojie Qu; Chao Jin; Miaoyue Zhang; Roland Bol; Jean Louis Morel; Zhihong Xu; et al. (Environmental Research, 2025)

Three-dimensional distribution and key drivers of neonicotinoid residues in hilly agricultural areas - Jiaxun Guo; Wenju Lei; Xu Liang; Haitang Wang; Weixiao Qi; Shuting Huang; Xiaoyu Chen; Shilong He (Environmental Research, 2025)

Electrospun polyvinyl alcohol/chitosan-ZIF-8@cyanidin cation-gallic acid multifunctional nanofilm for real-time visual monitoring of beef freshness - Qian Liang; Maonan Xu; Yalan Peng; Junwen Huang; Minjian Liao; Dongsong Lin; Yongkai Chen; Wuyi Zhou; Wenxu Zheng; Xianming Dong; Shuting Zhang (Chemical Engineering Journal, 2025)

High IGFL2 regulates ovarian cancer progression and the tumor immune microenvironment via the Warburg effect - Zhizai Chen; Dalong Song; Shuting Huang; Jinyu Chao; Junhong Huang; Ming Luo; Shanyang He (Molecular and Cellular Biochemistry, 2025)

Polystyrene Microplastics Induce Insulin Resistance and Glucose Metabolism Disorders in Grass Carp (Ctenopharyngodon idellus) via the Gut Microbiome–Metabolism Axis - Fubin Zhang; Shuting Huang; Xueting Chen; Zhendong Qin; Li Lin (Fishes, 2025)
Polystyrene microplastic (PS-MP) particles disrupt aquatic biological systems due to their persistence and high bioaccumulation potential, causing structural damage and inflammatory responses. PS-MPs also act as metabolic disruptors, affecting glucose metabolism and insulin signaling, although the mechanisms underlying these effects remain unclear. In this study, grass carp were exposed to 100 μg/L and 400 μg/L of polystyrene MPs for 30 days. Histopathological analysis showed the shortening of intestinal villi, vacuolization, and inflammatory infiltration. Antioxidant enzyme activities (SOD and CAT) were reduced, while the presence of tissue damage markers (GPT and GOT) was elevated, suggesting a biphasic oxidative stress response. Transcriptomic analysis revealed downregulation of genes related to metabolism and insulin signaling, especially at 400 μg/L. Gene set enrichment analysis (GSEA) highlighted pathways related to insulin resistance and type 2 diabetes, indicating the disruption of glucose metabolism. Microbiome analysis showed reduced diversity, expansion of Proteobacteria (opportunistic pathogens), and a decrease in beneficial bacteria like Bacillus. These shifts correlated with changes in the expression of key insulin signaling genes, emphasizing the role of host–microbiota interactions in metabolic imbalances. This study revealed that PS-MPs disrupt glucose metabolism and insulin signaling in grass carp through a combination of histological damage, oxidative stress, and microbiota dysbiosis.

Sensitive and selective simultaneous detection of ampicillin and chloramphenicol in foods with a SERS-activated molecularly imprinted capillary sensor - Sisi Tang; Ruili Li; Shuting Huang; Qi Liu; Xiaoqing Chen (Food Chemistry, 2025)

Chitosan/polyvinyl alcohol-based active film maintain the quality of farmed sea bass (Lateolabrax maculatus) during refrigerated storage: Inhibit lipid oxidation and maintain myofibrillar proteins conformation - Weiqing Lan; Shuting Liu; Xuening Chen; Jing Xie (Food Control, 2025)

Study on the degradation mechanism of compression performance of profiled SRC long columns under chloride corrosion - Yuanyuan Xu; Wenyuan Kong; Zhiquan Xing; Shuting Chen; Shujie Jiang; Wei Chen; Yu Chen (Engineering Structures, 2025)

All-screen-printed tactile sensor for robotic arm via polymeric thermal foaming - Xun Fu; Yugang Chen; Shuting Xie; Mengyu Cao; Qiang Zhao; Yixiao Liu; Yang Li; Shasha Wang; Xiaogang Cheng; Linghai Xie (Chemical Engineering Journal, 2025)

Variations in microbial community structure and extracellular enzyme stoichiometry in heavy metal-contaminated soil under different fertilization regimes - Xian Huang; Shuting Tang; Xiaoming Xin; Lixing Chen; Xinying He; Yueying Huang; Fangming Yu; Yi Li (Applied Soil Ecology, 2025)

Greenery strategies for reducing pedestrian particulate exposure along an open-flanked urban arterial road - Zhanyong Wang; Yanying Rao; Xinyuan Lin; Shuting Chen; Xisheng Hu (Urban Climate, 2025)

Performance of different corn hybrids and their corresponding water consumption analysis under various water management practices: Insights from experiments conducted under rain-shelters based on the TOPSIS method - Lei Wang; Jing Chen; Zhenyu Chu; Baizhao Ren; Bin Zhao; Peng Liu; Shuting Dong; Jiwang Zhang (European Journal of Agronomy, 2025)

Buprofezin causes early developmental toxicity of zebrafish (Danio rerio) embryos: morphological, physiological and biochemical responses - Shuting Qiang; Yufeng Che; Mingyang Lu; Yuan Tian; Lin Gao; Jingwen Chen; Tingzhang Hu (Aquatic Toxicology, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Magnetic field-enhanced activation of O2 by nano zero-valent iron for efficient treatment of copper-complexed wastewater - Lei Zou; Lu Wei; Yubei Liu; Mingjie Huang; Xiangling Zhang; Wenjiao Sang; Shuting Li; Chen Wang; Wei Xiang (Journal of Water Process Engineering, 2025)

Quantifying permafrost thawing and its impact on lake storage dynamics in the Qinghai-Tibet Plateau - Shuting Ji; Pan Wu; Lin Chen; Yingjie Yang; Xuehui Pi; Jeffrey M. McKenzie; Xiuyu Liang (Journal of Hydrology, 2025)

Genome-Wide Analysis of Ca2+-ATPases and their Salt Stress Responses in Sugar Beet - Shuting Liu; Sixue Chen; Inga R. Grin; Huizi DuanMu; Haiying Li (Sugar Tech, 2025)

Knockdown of the Clock gene in the liver aggravates MASLD in mice via inhibiting lipophagy - Shuhong Yang; Xinxin Ren; Jia Liu; Yan Lei; Minqian Li; Fang Wang; Shuting Cheng; Junjie Ying; Jie Ding; Xiaohui Chen (Molecular and Cellular Biochemistry, 2025)

ITIMCA: Image-text information and cross-attention for multi-modal cassava leaf disease classification based on a novel multi-modal dataset in natural environments - Huinian Li; Baoyu Chen; Jingjia Chen; Shuting Li; Feiyong He; Yingbiao Hu (Crop Protection, 2025)

Fate, source, and ecological risk of microplastic in the surface sediment of the Beibu Gulf, the Northern South China sea - Zuhao Zhu; Shuting Pang; Qiongyuan Su; Huihua Wei; Yi Qu; Jie Chen; Liangliang Huang (Marine Environmental Research, 2025)

A novel directed enzymolysis strategy for the preparation of umami peptides in Stropharia rugosoannulata and its mechanism of taste perception - Daoyou Chen; Mingli Rong; Shuting Tang; Chuanxi Zhang; Hao Wei; Zhaoting Yuan; Tingwei Miao; Hucheng Song; Haiming Jiang; Yan Yang; Lujia Zhang (Food Chemistry, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

Adaptive scootability index: Built environment, travel purpose and e-scooter preferred route - Shuting Chen; Zhejing Cao; Xiaohu Zhang (Journal of Transport Geography, 2025)

Effect of CNF ratio and pressure on structural and electrochemical performance of hybrid hydrogel for flexible free-standing electrode and sensors - Xiping Ding; Jiajia Shan; Shuting Yang; Junyan Liu; Chen Jiang; Shitao Yu; Qiong Wu (Carbohydrate Polymers, 2025)

Mitigating impacts of hot weather on outdoor workers by attaching phase change materials based on body mapping of physiology - Shuting Gu; Zhen Yang; Hongyu Chen; Wenwei Ma; Hongyi Gao; Ying Zhang; Jingxian Xu (Building and Environment, 2025)

Numerical Simulation Study on Hydrodynamic Characteristics of Offshore Floating Photovoltaics - Shuting Sui; Lu Cao; Yun Gao; Zhongyan Huo; Qi Chen (Journal of Marine Science and Engineering, 2025)
With the development of renewable energy and the utilization of marine resources, large-scale offshore floating photovoltaics have gradually attracted widespread attention. In order to develop offshore floating photovoltaics and promote sustainable development, it has become necessary to explore the hydrodynamic characteristics of floating photovoltaic units and floating arrays. In this work, based on the viscous flow theory, the Computational Fluid Dynamics (CFD) and the discrete element method (DEM) methods are used to analyze the hydrodynamics of the floating body unit of offshore floating photovoltaics. The influencing factors include mooring length, mooring radius, and floating unit length. In addition, the hydrodynamic performance of the floating body unit and the floating body array under different wave heights and periods is also discussed to explore the influence of environmental loads on the floating body unit and the floating body array. The results indicate that the mooring tension exhibits an opposite trend with the surge and heave motions when the mooring line length and radius are varied. The motion is found to be more pronounced when the floating body unit length is 0.4 times the wavelength. The heave motion of the floating body unit exhibits a strong linear relationship with wave height, increasing by 0.01 m for every 0.015 m increase in wave height. The motion of the floating body units on both sides connected to the mooring lines decreases as the array length increases.

Spatial and seasonal distribution, sources, and health risks of PM2.5 loaded per- and polyfluoroalkyl substances (PFASs) in a typical megacity - Shuting Li; Guanjiu Hu; Beibei Zhang; Xuewen Yao; Zhihuai Chen; Xiaosan Luo (Science of The Total Environment, 2025)

Nonlinear and threshold effects of the built environment, road vehicles and air pollution on urban vitality - Quang Cuong Doan; Jun Ma; Shuting Chen; Xiaohu Zhang (Landscape and Urban Planning, 2025)

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Remote sensing research on plastics in marine and inland water: Development, opportunities and challenge - Zhixiong Chen; Wei Si; Verner Carl Johnson; Saheed Adeyinka Oke; Shuting Wang; Xinlin Lv; Mou Leong Tan; Fei Zhang; Xu Ma (Journal of Environmental Management, 2025)

Energy, environmental footprints and economic benefit of substituting inorganic fertilizer with organic manure for winter wheat in Huanghuaihai Plain - Lei Wang; Jianjie Bi; Jing Chen; Baizhao Ren; Bin Zhao; Peng Liu; Shubo Gu; Shuting Dong; Jiwang Zhang (European Journal of Agronomy, 2025)

Transition metal doping of topological insulator Bi2Te2Se for application in zinc-ion batteries - Binbin Liu; Shuting Wang; Kemeng Yan; Yangyang Chen; Yuhui Ren; Haohui Xia; Ruiyong Chen; Junfeng Yan; Gang Wang (Chemical Engineering Journal, 2025)

Fluorine bismaleimide resin with outstanding piezoelectric characteristics for Structure-Function integrated composites - Bilin Zhang; Fei Liu; Shuting Chen; Liangkang Huang; Yuanyuan Zhong; Wei Fan; Jianwei Li (Chemical Engineering Journal, 2025)

A fast solid-phase microextraction scheme for in vivo monitoring of bio-accumulation and bio-transformation of arbidol in living plants - Jiating Zheng; Chao Chen; Yiquan Huang; Shuting Fang; Pengran Guo; Shuqin Liu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Base-driven dehydrohalogenation coupled with catalytic hydrodehalogenation as a novel strategy for rapid dehalogenation of halogenated organic compounds containing aliphatic C-X bonds - Shuting Qin; Chen Wu; Xuanxuan Ma; Sujing Liu; Ying Liu; Qing Li; Bingfei Yan; Chuanhai Xia (Journal of Environmental Chemical Engineering, 2024)

The decomposition of Fe-substituted rhodochrosite during coaling enhanced the transformation of NO before catalyst bed: Effect of instant-calcination - Shuting Cheng; Xuehua Zou; Daobing Shu; Tianhu Chen; Haibo Liu; Dong Chen (Journal of Environmental Chemical Engineering, 2024)

Enhanced electrocatalytic performance and exceptional durability facilitate the effective degradation of m-dinitrobenzene wastewaters utilizing a novel SS/PbO2-Y2O3-SiC electrode - Haoran Wu; Qiang Yu; Huixi Li; Zhen Chen; Wei Zhu; Shuting Li; Zhengming Dai; Qichun Xi; Jinjie Wei; Tingting Li (Journal of Environmental Chemical Engineering, 2024)

Fluorine polyimide nanofibrous composites with outstanding piezoelectric property for human motion monitoring - Shuting Chen; Jianwei Li; Bilin Zhang; Liangkang Huang; Keying Chen; Wei Fan; Junhao Liang (Chemical Engineering Journal, 2024)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

The synergistic effect of phototherapy and active substances on hair growth - Shuting Qiu; Zhi Pan; Xiao Jiang; Guowen Lv; Anqi Feng; Hongbo Chen (Journal of Photochemistry and Photobiology B: Biology, 2024)

Efficient and environmentally friendly uric acid voltametric sensor based on Ni-MOF and carboxylated multi-walled carbon nanotubes nanocomposites - Aiting Chen; Nana Tang; Yanping Wei; Shuting Shi; Chuanqin Zhou; Quanguo He; Jianhua Ding (Journal of Environmental Chemical Engineering, 2024)

Bi2MoO6/MWCNTs-COOH/GCE electrochemical probe for ultrasensitively and selectively detecting antibiotic norfloxacin - Shuting Shi; Chuanqin Zhou; Aiting Chen; Nana Tang; Kun Wan; Youwei Jiang; Jun Liu; Quanguo He; Li Cao (Chemosphere, 2024)

ARTP mutagenesis of Aureobasidium pullulans RM1603 for high pullulan production and transcriptome analysis of mutants - Ruoxuan Bai; Jiale Chen; Yaqiao Hao; Yiheng Dong; Keyao Ren; Ting Gao; Shuting Zhang; Fangxu Xu; Hongxin Zhao (Archives of Microbiology, 2024)

Seasonal changes in the phenolic compound contents and bioactivities in Betula platyphylla bark determined by soil properties - Quanxing Dong; Junrui Han; Shuang Wu; Yulin Pang; Yuwen Chen; Qianru Ji; Shengfang Wang; Shuting Zhao; Guanchao Cheng; Cholil Yun; Wenjie Wang; Huimei Wang (Flora, 2024)

V-doping and cation-vacancy engineering synergistically promote the electrocatalysis ability of NiFe-layered double hydroxides towards the oxygen evolution and urea oxidation reactions - Huixi Li; Qiang Yu; Xingdong Zhu; Haoran Wu; Zhengming Dai; Linxia Li; Wei Zhu; Shuting Li; Zhen Chen (Chemical Engineering Journal, 2024)

Soil aggregate size mediates the variations in the abundance and function of ammonia oxidizers in heavy metal-contaminated soil under different nitrogen fertilization regimes - Xian Huang; Shuting Tang; Meng Zeng; Zhongkai Qin; Jialiang Liang; Yuyuan Chen; Yamei Wu; Shuairen Chen; Fangming Yu; Yi Li (Applied Soil Ecology, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Spatial-Temporal Ship Pollution Distribution Exploitation and Harbor Environmental Impact Analysis via Large-Scale AIS Data - Xinqiang Chen; Shuting Dou; Tianqi Song; Huafeng Wu; Yang Sun; Jiangfeng Xian (Journal of Marine Science and Engineering, 2024)
Ship pollution emissions have attracted increasing attention in the maritime field due to the massive growth of maritime traffic activities. It is important to identify the ship emissions (SEs) magnitude and corresponding spatial and temporal distributions for the purposes of developing appropriate strategies to mitigate environment pollution. The aim of this study was to estimate ship pollution emissions with various typical merchant ship types under different sailing conditions. We estimated the emission variation with a ship traffic emission assessment model (STEAM2), and then the ship pollution emission distribution was further visualized using ArcGIS. We collected data from the automatic identification system (AIS) for ships in New York Harbor and further analyzed the spatiotemporal distribution of pollutant emissions from ships. The experimental results demonstrate that the ship pollutant emission volume in the New York Harbor area in 2022 was 3340 t, while the pollution in terms of CO, SO2, CXHX, PM10, NOX, and PM2.5 was 136, 1421, 66, 185, 1384, and 148 t, respectively. The overall SEs from container ships, passenger ships, and tankers account for a large amount of pollution discharge. The pollutant emissions of container ships are significantly greater than that of their counterparts. Moreover, the spatiotemporal distributions of ship pollutant discharge can vary significantly among different ship types and sailing conditions.

Dynamic coupling between cementation and porosity evolution of the Chang 8 tight sandstone reservoir, Ordos Basin: Insights from in-situ microanalysis - Ruiliang Guo; Weiwei Yang; Xiuqin Deng; Shuting Shi; Shutong Li; Junli Qiu; Jiaqiang Zhang; Junlin Chen; Lewei Hao; Xiaofeng Ma; Dongxu Ma; Peng Liu (Marine and Petroleum Geology, 2024)

Unveiling distinct influencing mechanisms of Br- on NDMA formation during ozonation of actual water Matrixes: Identification of precursors and brominated substance - Menglan Gao; Xiaobin Liao; Shuting Chen; Xiaoying Li; Yirou Zhang; Chao Chen; Huan Qi (Chemical Engineering Journal, 2024)

First Record of Partial Albinism in the Chinese Fanray, Platyrhina Sinensis (Elasmobranchii: Myliobatiformes: Platyrhinidae) - Yan Zhuang; Shuting Ke; Mingru Chen; Jiamei Xiao (Thalassas: An International Journal of Marine Sciences, 2024)
A female albino fanray specimen was collected by trawl from the southern Taiwan Strait on April 11, 2022. This unique individual was identified as the Chinese fanray, Platyrhina sinensis (Bloch & Schneider, 1801), based on morphological identification and DNA barcoding. It was classified as partial albinism (leucism) due to the absence of pigmentation in the skin and normal pigmentation in the irises. This specimen represents the first reported case of albinism within the family Platyrhinidae, providing valuable insights for physiological and ecological research on albino fish.

Trihalomethanes in global drinking water: Distributions, risk assessments, and attributable disease burden of bladder cancer - Yujie Shi; Wei Xia; Hongxiu Liu; Jiangtao Liu; Shuting Cao; Xingjie Fang; Shulan Li; Yuanyuan Li; Chao Chen; Shunqing Xu (Journal of Hazardous Materials, 2024)

Research progress on portable electrochemical sensors for detection of mycotoxins in food and environmental samples - Youwei Jiang; Yingyu Sima; Lei Liu; Chuanqin Zhou; Shuting Shi; Kun Wan; Aiting Chen; Nana Tang; Quanguo He; Jun Liu (Chemical Engineering Journal, 2024)

Aerosol impacts on summer precipitation forecast over the North China Plain by using Thompson aerosol-aware scheme in WRF: Statistical analysis and significant threat score improvements in polluted condition during June to August 2018 - Chunwei Guo; Dan Chen; Min Chen; Shuting Zhang; Jianping Guo; Zhanshan Ma (Atmospheric Research, 2024)

Investigation of the adsorption behavior and adsorption mechanism of pollutants onto electron beam-aged microplastics - Lei Chen; Haiyang Shao; Yingfei Ren; Chengkai Mao; Kang Chen; Hongyong Wang; Shuting Jing; Chengwei Xu; Gang Xu (Science of The Total Environment, 2024)

Restoring farmland to forest increases phosphorus limitation based on microbial and soil C:N:P stoichiometry-a synthesis across China - Hong Chen; Shuting Zhang; Changwei Ma; Yangzhou Xiang; Jianping Wu (Forest Ecology and Management, 2024)

Singlet oxygen promoted high mineralization of pharmaceutically active contaminants via persulfate-assisted mAg3PO4@g-C3N4 photocatalysis - Guanhan Chen; Wenhui Ding; Wenyi Dong; Hongjie Wang; Shuting Zhu; Tianzhe Liang; Cheng Luo; Yuxiong Huang (Chemical Engineering Journal, 2024)

Incorporating walking into ride-hailing: The potential benefits of flexible pick-up and drop-off - Fangyi Ding; Shuting Chen; Zhan Zhao (Transportation Research Part D: Transport and Environment, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Measuring and modeling the effects of green barriers on the spatial distribution of fine particulate matter at roadside - Xin Chen; Jie Wu; Wenbin Yang; Zhanyong Wang; Shuting Chen; Xisheng Hu; Kaifa Lu; Zhongmou Fan; Mei Lin; Pu Chen (Urban Climate, 2023)

Distribution and biodegradation of nonextractable polycyclic aromatic hydrocarbons in particle-size aggregates of field-contaminated soils - Ran Wei; Shuting Wei; Cheng Yao; Weifeng Chen; Liuming Yang; Jinzhi Ni (Journal of Soils and Sediments, 2023)

Single-chemical and mixture effects of multiple volatile organic compounds exposure on liver injury and risk of non-alcoholic fatty liver disease in a representative general adult population - Wei Liu; Shuting Cao; Da Shi; Linling Yu; Weihong Qiu; Weihong Chen; Bin Wang (Chemosphere, 2023)

Preparation of a novel Ti/TNAs/PbO2-PVDF-Er2O3 anode by Ti3+ self-doping TNAs and its electrocatalytic performance for hydroquinone degradation - Linxia Li; Wei Zhu; Huixi Li; Shuting Li; Lei Han; Lian Ren; Meng Wang; Xia Lu; Jiali Yuan; Shutong Li; Yize Wu; Zhen Chen; et al. (Journal of Environmental Chemical Engineering, 2023)

Alkalization-induced disintegration increased redox activity of solid humic acids and its soil biogeochemical implications - Caiqin Wang; Shuting Tang; Hangzhe Chen; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

N-methylpiperazine-diepoxyovatodiolide ameliorates peritoneal fibrosis via suppressing TGF-β/Smad and JAK/STAT signaling pathway - Min Mo; Yao Zeng; Yiqun Zeng; Shuting Li; Xiaoyang He; Xiaowen Chen; Qimei Luo; Mi Liu; Congwei Luo; Xianrui Dou; Fenfen Peng; Haibo Long (Chemico-Biological Interactions, 2023)

Isolation and characterization of an endophytic fungi from Zingiber officinale Rosc. and its activity to promote the growth of tissue culture ginger plantlets in bottles - Shuting Zhang; Yinghong Pei; Jiao Wang; Xiaolong Lin; Zizhong Tang; Lijun Zhou; Tao Chen; Shiling Feng; Chunbang Ding; Yanger Chen; Zhongwei Zhang; Shu Yuan; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Fabrication and characterizations of Zn-doped SnO2-Ti4O7 anode for electrochemical degradation of hexafluoropropylene oxide dimer acid and its homologues - Zehong Yang; Qiongfang Zhuo; Wenlong Wang; Shuting Guo; Jianfeng Chen; Yanliang Li; Sihao Lv; Gang Yu; Yongfu Qiu (Journal of Hazardous Materials, 2023)

Variations on the diazotrophic community in the rhizosphere soil of three dominant plant species in a lead–zinc mine area - Yi Li; Xuan Chen; Chijian Tang; Meng Zeng; Songying Li; Qiujie Ling; Kehui Liu; Jiangming Ma; Shuting Tang; Fangming Yu (Plant and Soil, 2023)

Synthesis of nano-Fe3O4/ZnO composites with enhanced antibacterial properties and plant growth promotion via one-pot reaction - Xiaohui Ji; Yuanyuan Han; Yinghua Wu; Ben Liang; Jinli Zheng; Shuting Ma; Chen Li; Haitao Xu; Shaobo Guo (Environmental Science and Pollution Research, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

One-pot fabrication of SF-DA@PVDF membrane for dye adsorption and oil-in-water emulsion separation - Peng Zhou; Shihong Zhang; Yi He; Jingcheng Wu; Liang Zhou; Xiangying Yin; Shuting Tian; Shuangshuang Li; Wen Chen (Journal of Environmental Chemical Engineering, 2023)

Biomimetic multienzyme nanocomplex for efficient cascade reactions - Hao Yuan; Shuting Yi; Lufan Jia; Sicheng Chen; Ting Guo; Tao Meng (Chemical Engineering Journal, 2023)

Investigating multi-way impacts of transportation on human footprint: Evidence from China - Shuting Chen; Yurui Li; Zhi Lu; Rui Li; Genying Chang (Environmental Impact Assessment Review, 2023)

Assembling nanocelluloses into fibrous materials and their emerging applications - Bing Wang; Shuting Qiu; Zehong Chen; Yijie Hu; Ge Shi; Hao Zhuo; Huili Zhang; Linxin Zhong (Carbohydrate Polymers, 2023)

Exposures to volatile organic compounds, serum vitamin D, and kidney function: association and interaction assessment in the US adult population - Wei Liu; Shuting Cao; Jixuan Ma; Da Shi; Linling Yu; Zi Ye; Meng Yang; Bin Wang; Weihong Chen (Environmental Science and Pollution Research, 2023)

Prevalence of coal worker’s pneumoconiosis: a systematic review and meta-analysis - Wei Liu; Ruyi Liang; Rixin Zhang; Bin Wang; Shuting Cao; Xing Wang; Jixuan Ma; Dongming Wang; Weihong Chen (Environmental Science and Pollution Research, 2022)

Effects of ocean warming and fishing on the coral reef ecosystem: A case study of Xisha Islands, South China Sea - Xinyan Zhang; Yuanchao Li; Jianguo Du; Shuting Qiu; Bin Xie; Weilin Chen; Jianjia Wang; Wenjia Hu; Zhongjie Wu; Bin Chen (Frontiers in Marine Science, 2022)
Global change has generated challenges for oceans, from individuals to the entire ecosystem, and has raised contemporary issues related to ocean conservation and management. Specifically, coral reef ecosystems have been exposed to various environmental and human disturbances. In this study, the Ecopath with Ecosim model was used to explore the impacts of ocean warming and fishing on Xisha Islands coral reef ecosystem in the South China Sea. The variables in this model included two ocean warming scenarios and three fishing scenarios. The model consisted of 23 functional groups including algae, coral, sea birds, and sharks. Our results showed that by the middle of the century, ocean warming and fishing led to a 3.79% and 4.74% decrease in total catch compared with 2009, respectively. In addition, the combined effects of ocean warming and fishing caused a 4.79% decrease in total catch, and the mean trophic level of catch was predicted to decrease by 6.01% under the SSP585-High fishing scenario. Reducing the fishing effort mitigates the effects of ocean warming on some species, such as large carnivorous fish and medium carnivorous fish; however, under low fishing effort, some functional groups, such as small carnivorous and omnivorous fish, have low biomass because of higher predation mortality.

Simulated warming and low O2 promote N2O and N2 emissions in subtropical montane forest soil - Xiong Yang; Yingmo Zhu; Yunjian Xu; Xiangnan Li; Shuting Zhang; Qindong Qian; Lingling Wang; Jianping Wu; Zhe Chen (Journal of Soils and Sediments, 2022)

Ectopic expression of grape hyacinth R3 MYB repressor MaMYBx affects anthocyanin and proanthocyanidin biosynthesis and epidermal cell differentiation in Arabidopsis - Jiangyu Wang; Boxiao Zhang; Shuting Tian; Han Zhang; Jiaxin Gong; Kaili Chen; Lingjuan Du (Horticulture, Environment, and Biotechnology, 2022)

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Long-term impact of ambient air pollution on preterm birth in Xuzhou, China: a time series study - Sha Li; Lei Peng; Xiaochang Wu; Geng Xu; Peng Cheng; Jingwen Hao; Zhaohui Huang; Meng Xu; Shuting Chen; Chao Zhang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Molecular characterization of miRNA genes and their expression in Dimocarpus longan Lour - Yuling Lin; Yan Chen; Youjing Zeng; Shuting Zhang; Zihao Zhang; YuKun Chen; Jiawei Gong; Zhongxiong Lai (Planta, 2021)

Determining the contributions of climate change and human activities to the vegetation NPP dynamics in the Qinghai-Tibet Plateau, China, from 2000 to 2015 - Bing Guo; Baomin Han; Fei Yang; Shuting Chen; Yue Liu; Wenna Yang (Environmental Monitoring and Assessment, 2020)

Dimethylaminomicheliolide ameliorates peritoneal fibrosis through the activation of autophagy - Shuting Li; Fenfen Peng; Wangqiu Gong; Jiayu Wu; Yuxian Wang; Zhaozhong Xu; Wenting Liu; Hongyu Li; Bohui Yin; Ying Zhang; Sijia Chen; Congwei Luo; et al. (Journal of Molecular Medicine, 2019)

Temporal characteristics detection and attribution analysis of hydrological time-series variation in the seagoing river of southern China under environmental change - Lihua Chen; Yan Wang; Billel Touati; Haopeng Guan; Gang Leng; Weifu Liu; Shuting Lv; Shuping Huang; Zihao Pan (Acta Geophysica, 2018)

Production of eicosapentaenoic acid (EPA, 20:5n-3) in maize (Zea mays L.) through the alternative ∆8 desaturation pathway mediated by particle bombardment - Chenchen Wang; Xiao Yang; Haizhen Ma; Jiang Liu; Jing Chen; Jiedao Zhang; Shuting Dong; Baoxiu Qi; Xinzheng Li (Acta Physiologiae Plantarum, 2017)

Copper tolerant Elsholtzia splendens facilitates Commelina communis on a copper mine spoil - Ruyi Yang; Fuyu Guo; Shuting Zan; Gang Zhou; Wibke Wille; Jianjun Tang; Xin Chen; Jacob Weiner (Plant and Soil, 2015)

Molecular characterization of heat–shock protein 90 gene and its expression in Gobiocypris rarus juveniles exposed to pentachlorophenol - Qiuping Liu; Shuting Huang; Chuan Deng; Li Xiong; Xiang Gao; Yun Chen; Chunqing Niu; Yan Liu (Fish Physiology and Biochemistry, 2015)

Upregulation of SET Expression by BACE1 and its Implications in Down Syndrome - Xiaozhu Zhang; Yili Wu; Xiaoling Duan; Wei Chen; Haiyan Zou; Mingming Zhang; Shuting Zhang; Fang Cai; Weihong Song (Molecular Neurobiology, 2015)

Factors affecting summer maize yield under climate change in Shandong Province in the Huanghuaihai Region of China - Guoqing Chen; Hongjun Liu; Jiwang Zhang; Peng Liu; Shuting Dong (International Journal of Biometeorology, 2012)

Effects of Developmental Exposure to TiO2 Nanoparticles on Synaptic Plasticity in Hippocampal Dentate Gyrus Area: an In Vivo Study in Anesthetized Rats - Xiaoyan Gao; Shuting Yin; Mingliang Tang; Jutao Chen; Zhongfei Yang; Wencai Zhang; Liang Chen; Bo Yang; Zhifeng Li; Yingying Zha; Diyun Ruan; Ming Wang (Biological Trace Element Research, 2011)

Study and Application of the Interaction Between Asymmetrical Porphyrin and Ascorbic Acid - Shuting Sun; Dan Wu; Qin Wei; Yanyan Han; Xin Chen; Yunxia Shen; Peihua Zhu; Bin Du (Journal of Fluorescence, 2009)